2020
DOI: 10.1002/mdc3.12876
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Deep Brain Stimulation for Acquired Hemidystonia

Abstract: Background Background: The cerebellum's role in dystonia is increasingly recognized. Dystonia can be a disabling and refractory condition; deep brain stimulation can help many patients, but it is traditionally less effective in acquired dystonia. New surgical targets would be instrumental in providing treatment options and understanding dystonia further. Objective Objective: To evaluate the efficacy of deep brain stimulation of the cerebellum in acquired dystonia. Methods Methods: We report our management of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 32 publications
1
47
0
Order By: Relevance
“…If prolonged muscle contractions are a prerequisite for DBS working, then cerebellar stimulation could also be beneficial for different forms of dystonia, a heterogeneous disorder in which specific abnormalities, such as widened EMG signals and muscle co-contractions, tend to occur as consistent features 43 . Preliminary studies in humans 78 and mice 26 indeed support the utility of cerebellar stimulation for dystonia. How effective therapeutic cerebellar DBS would be for neurodegenerative ataxias depends on which circuit properties change and how they might mediate the positive effects of stimulation because Purkinje cell loss alone does not block cerebellar DBS effectiveness 18 .…”
Section: Discussionmentioning
confidence: 79%
“…If prolonged muscle contractions are a prerequisite for DBS working, then cerebellar stimulation could also be beneficial for different forms of dystonia, a heterogeneous disorder in which specific abnormalities, such as widened EMG signals and muscle co-contractions, tend to occur as consistent features 43 . Preliminary studies in humans 78 and mice 26 indeed support the utility of cerebellar stimulation for dystonia. How effective therapeutic cerebellar DBS would be for neurodegenerative ataxias depends on which circuit properties change and how they might mediate the positive effects of stimulation because Purkinje cell loss alone does not block cerebellar DBS effectiveness 18 .…”
Section: Discussionmentioning
confidence: 79%
“…The deviation of electrode placement in DN stimulation due to the large size of the DN may account for the variable effects observed in those reported cases and in our case. The stimulation parameters (1.85~2.45 V, 50 µs, 130 Hz) used in this study were lower than most previously reported stimulation parameters of cerebellar DBS studies (Table 4) [ [13][14][15][16][17][18]. The selection of the electrode lead and correct lead placement may be the key step for the low parameter in our study.…”
Section: Discussionmentioning
confidence: 70%
“…Shiro Horisawa et al also reported a patient with generalized dystonia who responded well to SCP DBS than DN DBS [16]. The study reported by Brown et al showed the validity of DN DBS in treating hemidystonia; however, it is worth noting that the active contacts were in close proximity to or within SCP [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this procedure was abandoned for unknown reasons. To date, there have been few reports on deep cerebellar stimulation (8)(9)(10)(11). Sokal et al reported the treatment of secondary dystonia by anterior cerebellar DBS, which resulted in a 42.8% improvement according to the Unified Dystonia Rating Scale (10).…”
Section: Introductionmentioning
confidence: 99%